2002
DOI: 10.3104/reports.132
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in coping strategies of parents of children with Down syndrome

Abstract: -Little research has been conducted on the reactions of parents, and fathers in particular, following the birth of a child with Down syndrome. Previous studies suggest that gender differences exist in coping strategies and a number of theories have supported this. The current study is informed by Pleck's (1981) Gender Role Strain model which attempts to explain the different socialisation processes males encounter which influence their development in our society. Questionnaires from Carver, Scheier and Weintra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 21 publications
1
24
1
4
Order By: Relevance
“…Women are more likely than men to utilize coping strategies to deal with stressful situations (Affleck et al, 1999;Matheny et al, 2005;Tamres et al, 2002); also, women are more likely to engage in religious coping practices than men (Dunn & Horgas, 2000, 2004Ellison & Taylor, 1996). Previous research has also found that women tend to most often utilize emotion-focused coping strategies (Affleck et al, 1999;Matud, 2004;Sullivan, 2002;Tamres et al, 2002). Pargament, Ano, and Wachholtz (2005) suggest that religious beliefs and practices offer individuals a variety of resources which may aid in coping with and overcoming stressful or difficult situations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women are more likely than men to utilize coping strategies to deal with stressful situations (Affleck et al, 1999;Matheny et al, 2005;Tamres et al, 2002); also, women are more likely to engage in religious coping practices than men (Dunn & Horgas, 2000, 2004Ellison & Taylor, 1996). Previous research has also found that women tend to most often utilize emotion-focused coping strategies (Affleck et al, 1999;Matud, 2004;Sullivan, 2002;Tamres et al, 2002). Pargament, Ano, and Wachholtz (2005) suggest that religious beliefs and practices offer individuals a variety of resources which may aid in coping with and overcoming stressful or difficult situations.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have documented significant differences in the ways that men and women cope with stress (Affleck et al, 1999;Matheny, Ashby, & Cupp, 2005;Matud, 2004;Sullivan, 2002;Tamres, Janicki, & Helgeson, 2002). Women are more likely than men to utilize coping strategies to deal with stressful situations (Affleck et al, 1999;Matheny et al, 2005;Tamres et al, 2002); also, women are more likely to engage in religious coping practices than men (Dunn & Horgas, 2000, 2004Ellison & Taylor, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Levin, Taylor and Chatters (1994) note: 'in the context of a stress and coping paradigm, differential patterns and levels of adoption of family and social roles may predispose women and men to different levels of stress, and as a consequence, to differences in how they employ religion as a coping method' (p. 138). Studies involving the 'turning to religion' scale, a distinct measure of an aspect of emotion-focused coping of the COPE inventory (Carver, Scheier, & Weintraub, 1989), have significant gender differences between parents coping with a child with a mental retardation (Sullivan, 2002) for example, and patients dealing their HIV/ AIDS status (Olley et al, 2003), with women employing more 'turning to religion' coping than men. We base our hypothesis on the literature that women have been found to be more religious/spiritual than men.…”
Section: Introductionmentioning
confidence: 99%
“…Nesse sentido, Sullivan (2002) buscou identificar possíveis diferenças nas estratégias de coping de pais e mães ingleses de crianças com SD. As mães apresentaram escores mais altos do que os pais nas estratégias de coping de busca por apoio instrumental e emocional, foco sobre e expressão das emoções, e supressão de atividades competitivas.…”
Section: Síndrome De Down: Breve Caracterizaçãounclassified